2012
DOI: 10.2337/dc11-2170
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Function Preservation After 3.5 Years of Intensive Diabetes Therapy

Abstract: OBJECTIVETo assess β-cell function preservation after 3.5 years of intensive therapy with insulin plus metformin (INS group) versus triple oral therapy (TOT group) with metformin, glyburide, and pioglitazone.RESEARCH DESIGN AND METHODSThis was a randomized trial of 58 patients with treatment-naïve newly diagnosed type 2 diabetes. All patients were treated with insulin and metformin for a 3-month lead-in period followed by random assignment to the INS or TOT group. β-Cell function was assessed using a mixed-mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 21 publications
1
69
0
6
Order By: Relevance
“…Other reports with different study designs and therapeutical algorithms (e.g. longer duration of insulin therapy, use of premix or basal insulin regimens) have basically indicated the same point: insulin therapy has a beneficial effect on preservation of beta cell secretory function, even in the long term (26)(27)(28)(29). Similar to our findings, a recent paper showed that chronic treatment with longacting basal insulin improved both first-and second-phase insulin secretion (evaluated by intravenous glucose tolerance test) in hyperglycemic patients with type 2 diabetes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports with different study designs and therapeutical algorithms (e.g. longer duration of insulin therapy, use of premix or basal insulin regimens) have basically indicated the same point: insulin therapy has a beneficial effect on preservation of beta cell secretory function, even in the long term (26)(27)(28)(29). Similar to our findings, a recent paper showed that chronic treatment with longacting basal insulin improved both first-and second-phase insulin secretion (evaluated by intravenous glucose tolerance test) in hyperglycemic patients with type 2 diabetes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Harrison et al (11) found that after an initial 3-month therapy with biphasic insulin and metformin, treatment of 58 newly diagnosed patients on either continued insulin/metformin or triple oral therapy (metformin/glyburide/pioglitazone) had stabilized measures of insulin secretion such that they neither differed from baseline nor differed between treatment arms. In patients with established T2DM, we previously showed that the improved b-cell function achieved with 4-8 weeks of prerandomization IIT was completely lost during the 48 weeks of subsequent treatment with either metformin/ sitagliptin combination therapy or metformin alone (10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the glucose-lowering activity of an antidiabetic medication can further confound such evaluation in patients with T2DM in whom improved b-cell function may be due to the elimination of glucotoxicity rather than to actual b-cell preservation (9). In this context, short-term treatment with insulin therapy has been proposed as a strategy for eliminating glucotoxicity before randomization, thereby creating a level playing field upon which to objectively evaluate the potential b-cell protective capacity of antidiabetic medications (9)(10)(11).…”
mentioning
confidence: 99%
“…In 2013, an expert point-counterpoint discussion presented arguments for and against the use of incretin-based therapies, given conflicting safety data available at the time (72,73). The impact of intensive insulin treatment on the preservation of b-cell function was highlighted in studies reported in 2012 in patients with newly diagnosed type 2 diabetes (74) and in 2013 in patients with newonset type 1 diabetes (75). Recent review articles have included a summary of data on natriuretic peptides (76), a history of hyperosmolar hyperglycemic state (77), and an update on the effects of DPP-4 inhibition on microvascular complications (78).…”
Section: To the Present: Building On A Tradition Of Excellencementioning
confidence: 99%